ManagInn : creación de un apoyo para gestores de la innovación en equipos de diseño (2020)
Purpose - The purpose of this research is to improve in different aspects the experience that innovation teams have within a company. Currently, they have to rely on several web platforms to achieve a process of innovation, each of these focuses on one specific thing but none manages to bring together everything necessary for the teams and managers. This is how we saw what the strengths of each one were and applied them in one place, so that the teams and managers can resort to a single space to do what they need. Design/methodology/approach - For this project the methodology applied is based on the double diamond of the Design Council. Where throughout one year the 4 stages were applied (Discovery, Definition, Development, Delivery), to reach the results exposed today. Different tools were applied, such as interviews and observation methods, during the first two phases in order to get to know our end users, managers and innovation teams better and thus achieve a product that they would consider valuable. In the last two parts, constant user tests and usability tests were carried out to verify that the product achieved met the objectives set and to always be aware of errors that could be corrected. The users used for these tests and interviews were students from the Master's Degree in Innovation at Icesi University, and directors or managers of innovation who hold positions within companies and have years of experience in the field.